Working capital management and profitability: evidence from Indonesian manufacturing companies - Irfan Aryawan; Astiwi Indriani (Diponegoro International Journal of Business, 2020)
The aims of this study is to analyze the relationship between working capital management and profitability (return on assets) as a dependent variable and cash conversion cycle (CCC), inventory conversion period (ICP), average collection period (ACP) and average payment period (APP) as independent variables with leverage, liquidity, and size as the controlling variables. The sample of this study are manufacturing companies in the Indonesian Stock Exchange 2013-2017. The analysis using OLS showed that the ACP has a negative and significant effect on ROA and the APP has a positive and significant effect on ROA, meanwhile CCC and ICP has a negative and insignificant effect on ROA.